2021
DOI: 10.21037/ht-20-28
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ use of mobile applications in the first year of parenthood: a narrative review of the literature

Abstract: Parent's use of apps to support their parenting is on the rise. The purpose of this narrative review of the literature is to explore the characteristics of research on parents' app use in the first year of parenthood, types of apps available to parents, and the factors that encourage or discourage parents' app use. A narrative review of the literature and thematic analysis of the full-text English language articles between January 2000 and December 2019 relating to parents' use of apps in the first year of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Mobile apps are another avenue to explore for the RecMap, as there is a rise in parents using apps to support their parenting [ 40 ]. This modality is versatile and can encompass multimedia elements (eg, graphics and videos) to engage users and push notifications to alert users of new information or updates on the application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile apps are another avenue to explore for the RecMap, as there is a rise in parents using apps to support their parenting [ 40 ]. This modality is versatile and can encompass multimedia elements (eg, graphics and videos) to engage users and push notifications to alert users of new information or updates on the application.…”
Section: Discussionmentioning
confidence: 99%
“…This is an interesting feature to consider given that the RecMap contains living recommendations that are frequently updated or changed. It is equally important for parents that mobile apps are of high quality, relevant, visually appealing, interactive, and seamless (ie, easy to navigate, do not freeze, or crash); otherwise, there is a risk that flawed apps will be deleted by end users within minutes after being downloaded [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mental health was a highly valued topic to be included in an ideal app, which seems to be under-addressed from the perspective of both perinatal women and health professionals in the apps available. A recent review on apps for the first year of parenthood also identified supporting parents’ mental health as a need not being addressed in parenting apps ( 42 ). The fact that both perinatal women and health care professionals are open to this content is an opportunity for mental health promotion, prevention, and early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Including the partner in the apps and not addressing the mothers exclusively regarding infant care probably will contribute to balancing the load placed on mothers and promote co-parenting. Supporting the couple during the transition to parenthood or the addition of a new infant has also been identified as a need in a review on the use of parenting apps ( 42 ), and it seems of great importance for the whole family’s health. On the other hand, considering the association between social support and parenting stress ( 43 ), an app should also emphasize the importance of strengthening the social network and guiding on how to do so (e.g., training communication skills).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid rise in cell phone coverage globally [25] and the introduction of mobile computing devices such as smartphones and tablets have created new opportunities for health and social systems to engage with patients and parents at scale [26][27][28], resulting in a rapid growth in the development of software apps for these platforms [29][30][31][32][33][34]. Additionally, new mobile phone contracts that offer low-income families access to basic messaging software (such as WhatsApp and Facebook messengers) without formal data contracts have also contributed to the expansion.…”
Section: Introductionmentioning
confidence: 99%